2017
DOI: 10.1002/iub.1639
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of hedgehog pathway is required for the protective effects of magnesium isoglycyrrhizinate against ethanol‐induced hepatocyte steatosis and apoptosis

Abstract: Alcoholic liver disease (ALD), characterized by excessive deposition of lipids in hepatocytes, causes heavy health burden personally and socially. Mechanistically, hedgehog signaling was activated during the development of ALD, and exerted compelling role in regulating lipometabolism. The current promising intervention strategy is inhibition of lipid accumulation and apoptosis in hepatocytes. Magnesium isoglycyrrhizinate (MgIG) has been widely used in various liver diseases for its good hepatoprotective activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…As a protective agent for liver cells, Magnesium Isoglycyrrhizinate (MgIG) has an effect of protecting liver cell membrane. We previously reported that MgIG protected the ethanol‐induced hepatocyte injury and further clarified the potential molecular mechanisms . Interestingly, whether MgIG improves the inflammatory microenvironment of liver fibrosis and activates the HSCs apoptosis has never been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…As a protective agent for liver cells, Magnesium Isoglycyrrhizinate (MgIG) has an effect of protecting liver cell membrane. We previously reported that MgIG protected the ethanol‐induced hepatocyte injury and further clarified the potential molecular mechanisms . Interestingly, whether MgIG improves the inflammatory microenvironment of liver fibrosis and activates the HSCs apoptosis has never been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…We speculated that DHA as a natural product could regulate the serum TC through some other mechanisms, which is worthy of further investigations. In recent years, the important transcriptional regulators including PPARα and SREBP‐1c, and their downstream targets, such as FAS and CPT1, involved in β‐oxidation and fatty acid synthesis, have been identified as specific targets of ethanol action in the liver . We provide evidence suggesting that lipin‐1, a vital regulator, may be responsible for ethanol‐mediated impairment of a hepatic signaling network, influenced by DHA through regulation of its nucleocytoplasmic shuttling.…”
Section: Discussionmentioning
confidence: 86%
“…Liver histology was examined using hematoxylin‐eosin (H&E) staining as we previously described . Immunohistochemistry of liver section was performed by using antibodies against CD45, F4/80, and Cleaved‐caspase3 according to the previous study .…”
Section: Methodsmentioning
confidence: 99%
“…Appearing in an early materia medica manuscript, "Shennong's Classic Materia Medica," it has since been applied across China in many contexts as a result of its characteristics (Yang et al, 2016). MgIG, a magnesium salt of the 18-alpha-glycyrrhizic acid stereoisomer and classified as a new molecular compound identified in the roots of the Glycyrrhiza glabra (licorice) tree (Lu, Xu, et al, 2017), is associated with anti-inflammatory and antioxidant properties and hepatic protection and liver function enhancement (He et al, 2010;Sun et al, 2007). For the inhibition of ethanol-induced lipid peroxidation, MgIG has also been used as a pharmaceutical for liver protection (Xie et al, 2015).…”
Section: Discussionmentioning
confidence: 99%